An ethnographic content analysis of children’s fiction picture books reflecting African American culture published 2001-2005 - Nephew, Irene J. (Kansas State University, 2009)
An ethnographic content analysis was conducted to explore the African American cultural content contained in the text of picture books portraying African Americans published 2001 through 2005. The picture books were limited to beginning readers, stories in rhyme and poetry, historical fiction, fictional biography, and contemporary fiction portraying African Americans and set in the U.S. The books were categorized based on the genre to which they belong and classified as generic books or books with African American cultural content. The African American cultural content in the books in the study was compared to the cultural content contained in picture books in a survey conducted by Rudine Sims Bishop in 1982. Differences between the work of African Americans and non African Americans are discussed. A data collection instrument was constructed and used by several additional raters to test the reliability of the instrument. Each additional rater was given an operational definition for generic books and books with cultural content. The raters were each given one book to evaluate. The research revealed (1) that more than half of the picture books published during the period of this study were classified as generic, (2) in most cases, only the books written by African Americans contained cultural content and (3) more than half of the picture books with cultural content are classified as historical fiction. (4) Although it is possible for a non African American to write an authentic picture book with cultural content, such books are usually the result of in depth research. (5) During the period of this study, not all generic picture books were written by non African Americans; some African American authors choose to write generic books portraying African Americans with minimal content specific to African American culture.
Keywords: Multicultural literature; African American childrens' literature; Education, Bilingual and Multicultural (0282); Education, Curriculum and Instruction (0727); Education, Language and Literature (0279)